1993
DOI: 10.1021/bi00077a021
|View full text |Cite
|
Sign up to set email alerts
|

Optical activity of hemoproteins in the Soret region. Circular dichroism of the heme undecapeptide of cytochrome c in aqueous solution

Abstract: Different possible mechanism for generation of optical activity of hemoproteins in the Soret region are reconsidered. The heme undecapeptide of cytochrome c does not contain aromatic amino acid residues, so its considerable optical activity cannot be due to coupling of heme pi pi * transitions with those of aromatic residues. CD data for the heme undecapeptide and for ferrimyoglobin and some of their complexes with small molecules are presented and critically compared. Symmetrically coordinated imidazole compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 36 publications
7
105
0
Order By: Relevance
“…This suggests that the two proteins have similar but not identical heme pocket structures. In hemoproteins, the Soret CD spectrum is strictly correlated with the heme pocket conformation [24]. In particular, for cyt c the 416-nm Cotton effect is associated to the F82-and M80-heme interaction and is considered a probe of the environment on the M80 side of the heme pocket in the native protein [25,26].…”
Section: Ferric Cyt Cmentioning
confidence: 99%
“…This suggests that the two proteins have similar but not identical heme pocket structures. In hemoproteins, the Soret CD spectrum is strictly correlated with the heme pocket conformation [24]. In particular, for cyt c the 416-nm Cotton effect is associated to the F82-and M80-heme interaction and is considered a probe of the environment on the M80 side of the heme pocket in the native protein [25,26].…”
Section: Ferric Cyt Cmentioning
confidence: 99%
“…Nevertheless, CD spectra of this region are strongly dependent on the immediate conformational environment of the heme group and provide a sensitive indicator of small scale conformational changes in the protein (45). Denaturation studies have indicated that the trough at 420 nm relates to the heme iron-Met (80) bond in cyt c (46).…”
Section: Effects Of Atp On the Binding Of Cyt C To Liposomes-atmentioning
confidence: 99%
“…4). FAD optical activity is induced by dipole-dipole interactions of the flavin with the ribityl side chain, the peptide backbone, and side-chains of tyrosine, tryptophan, and to a lesser extent, methionine (28,29). The ␣T266M ETF circular dichroism spectrum reflects the loss of resolution in the visible absorption spectrum.…”
Section: Expression and Stabilization Of Mutants-initial Attempts Tomentioning
confidence: 99%